Causal Attribution, Benefits Sharing, and Earnings Management* - Helikum, Lukas J.; Tan, Hun‐Tong; Xu, Tu (Contemporary Accounting Research, 2022)
ABSTRACT We conduct two experiments to investigate the joint effect of two justification factors of earnings management—namely, attribution for the firm's underperformance and benefits accruing to other employees from inflating reported earnings. This investigation is important because prior research examines the effects of individual justification factors, whereas real‐world settings entail more complexity involving multiple justification factors. In Experiment 1, we predict and find that managers are more likely to manage earnings when the firm's underperformance is caused by an external event and misreported earnings benefit other employees besides the reporting manager. Furthermore, we show that the extent to which participants use moral justifications mediates the effect of benefits sharing on earnings management, but only when causal attribution is external, and that it mediates the effect of causal attribution on earnings management, but only when benefits are shared. In Experiment 2, we use a neutral control condition that makes no mention of inconsistent incentives to demonstrate that it is the combination of causal attribution and benefits sharing that triggers earnings management. We contribute to the accounting and psychology literature by proposing and testing a theory that explains how multiple justification factors interact to cause opportunistic behavior. Our results suggest that policy‐makers and governing parties should consider developing a holistic view of possible justification factors, focusing on situational opportunities created by combinations of factors rather than individual factors alone.